2001
DOI: 10.1021/ja015944i
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of the Thermotropic Cubic Phase:  Insights from Monoacetylide Complexes of Pt(II)

Abstract: In the liquid crystal phase behavior of surfactants, cubic phases are common and can, in principle, be found between any pair of adjacent phases. 1 In a binary water/surfactant phase diagram, the formation of phases as a function of water content depends on interactions between the polar headgroups and the water solvent, and also on the size of the polar headgroup versus the volume occupied by the hydrophobic chains. In an organized assembly of these surfactant molecules, one can imagine that a surface between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…18) which required the use of three equivalents of acetylene and rather short reaction times (sometimes only ten minutes). 32 The mesomorphism of these new complexes was established by optical microscopy and, perhaps unsurprisingly, we found that the bis(acetylide) complexes showed a nematic phase as we had found with the alkanoate complexes, although curiously, we were also able to observe a SmC phase, too. However, we were most keen to find out about the behaviour of the monoacetylide complexes, for now we had direct analogues of the silver complexes except that these platinum complexes have a single chain but no ionic component to the metal-ligand interaction.…”
Section: Controlling the 'Bends'supporting
confidence: 61%
See 1 more Smart Citation
“…18) which required the use of three equivalents of acetylene and rather short reaction times (sometimes only ten minutes). 32 The mesomorphism of these new complexes was established by optical microscopy and, perhaps unsurprisingly, we found that the bis(acetylide) complexes showed a nematic phase as we had found with the alkanoate complexes, although curiously, we were also able to observe a SmC phase, too. However, we were most keen to find out about the behaviour of the monoacetylide complexes, for now we had direct analogues of the silver complexes except that these platinum complexes have a single chain but no ionic component to the metal-ligand interaction.…”
Section: Controlling the 'Bends'supporting
confidence: 61%
“…Thus, while we cannot attribute cubic phase formation solely to intermolecular electrostatic interactions, we can identify these interactions as crucial. 32 Now, is this explanation specific to these complexes, or does it find resonance in the structures of other calamitic mesogens which form cubic phases? The answer, we believe, is that the explanation is not strictly specific, rather that it hints at another factor.…”
Section: Discussionmentioning
confidence: 99%
“…After the pioneering work on hexakis­(phenyl­ethynyl)­aryl derivatives with either a benzene, naphthalene, or triphenylene central ring, more recent works include some hexakis­(4-ethylene oxide benzoate)­triphenylenes mixed with alkali salts, phenylene ethynylene macrocycles, , phenyl­ethynyl­benzene derivatives, , as well as truxenes, thiatruxenes, and oxatruxenes . LC systems with structures deviating slightly from a conventional disc, such as triphenylene twins, nonuniformly alkyl-chains substituted phthalo­cyanines and di­ben­zo­tetra­aza­[14]­annulenes, cyclo­[6]­aramides, and shape-persistent aromatic oligoamides, soft spacer-connected triphenylene-pentaalkynylbenzene dyads, as well as some polycatenar mesogens, with unsymmetrical substitution or lateral chains have also been reported to exhibit a nematic mesomorphism. Very recently, new materials for molecular electronics have shown high performances in conjunction with the appearance of nematic properties.…”
Section: Introductionmentioning
confidence: 99%
“…31 Among them, the self-assembly features of hydrophobic Pt(II) complexes with acetylide, [32][33][34][35][36] bidentate, [37][38][39] tridentate N-donor, [40][41][42] and cyclometalating ligands [43][44][45] are relatively well understood. 31 In contrast, their hydrophobic counterparts featuring non-chelating ligands and, in particular, bis(pyridyl) Pt(II) complexes have been limited to liquid crystalline materials [46][47][48] and hydrogen-bonded metallogelators. 49,50 Thus, there is a need for a deeper understanding of this class of Pt(II) complexes, in which not only the nature of the metal ion but also a wide range of weak unconventional forces stemming from the ligands attached to the metal fragment 51,52 anticipate the discovery of new supramolecular synthons.…”
Section: Introductionmentioning
confidence: 99%